2000
DOI: 10.1246/bcsj.73.67
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Heat Capacities and Ferromagnetic Phase Transition of the Organic Free Radical Ferromagnet, 4-(4-Chlorobenzylideneamino)-2,2,6,6-tetramethylpiperidin-1-oxyl (CATMP)

Abstract: Heat capacities of the organic free radical ferromagnet, 4-(4-chlorobenzylideneamino)-2,2,6,6-tetramethylpiperidin-1-oxyl (CATMP) have been measured in the temperature range between 0.1 and 311 K. A ferromagnetic phase transition was observed at 0.28 K and a heat capacity hump was found above the transition temperature. This hump is due to the short-range order characteristic of low-dimensional magnetic spin systems. The enthalpy and entropy gains due to the ferromagnetic phase transition were estimated to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Nogami et al synthesized many TEMPO radicals and discovered bulk ferromagnetic behaviors in some TEMPO crystals (Figure ). Among them, Miyazaki et al measured heat capacities of CATMP and 4-benzylideneamino-TEMPO (BATMP) crystals and found ferromagnetic phase transitions at T C = 0.28 and 0.19 K, respectively. Figure illustrates the excess heat capacity of CATMP plotted on logarithmic and normal scales.…”
Section: 2 Tempo Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nogami et al synthesized many TEMPO radicals and discovered bulk ferromagnetic behaviors in some TEMPO crystals (Figure ). Among them, Miyazaki et al measured heat capacities of CATMP and 4-benzylideneamino-TEMPO (BATMP) crystals and found ferromagnetic phase transitions at T C = 0.28 and 0.19 K, respectively. Figure illustrates the excess heat capacity of CATMP plotted on logarithmic and normal scales.…”
Section: 2 Tempo Radicalsmentioning
confidence: 99%
“…Solid curves indicate the heat capacities calculated from the HT series expansion for the S = 1/2 2D ferromagnetic Heisenberg model of square lattice with J / k = 0.42 K. Broken curves show the heat capacities derived from the spin-wave theory for 3D ferromagnets. Reprinted with permission from ref . Copyright 2000 The Chemical Society of Japan.…”
Section: 2 Tempo Radicalsmentioning
confidence: 99%
“…Adiabatic heat capacity calorimetry for magnetic substances is one of the most powerful methods for investigation of their magnetic properties, because one can gain the information about precise magnetic phase transition temperatures, degrees of spin ordering, spin−spin interaction, magnetic dimensionality, and type of magnetism. The Sorai group has extensively elucidated the magnetic properties of several organic free radical magnets by adiabatic heat capacity calorimetry. 4a,b,e,f,9h In the present paper, we report the precise and accurate calorimetric studies of polycrystalline BABI to reveal further aspects of its magnetic properties, beyond those obtained by magnetic study …”
Section: Introductionmentioning
confidence: 90%
“…Particularly, pure organic magnets have attracted many organic and physical chemists, in efforts to design specific molecule-based structures. So far, many examples of organic free radical magnets have been prepared and investigated. …”
Section: Introductionmentioning
confidence: 99%
“…Our research group has so far revealed interesting magnetisms of some TEMPO derivative crystals by adiabatic calorimetry. 9a,9b,9d, 13,14 The aim of the present work is to elucidate the magnetic properties of the BATMP crystal similar to 4-(4-chlorobenzyli- * To whom correspondence should be addressed. Tel: +81-6-6850-5523.…”
Section: Introductionmentioning
confidence: 99%